A Video Interview of Buz Brock - Bruce Mizrach (Rutgers University, Department of Economics, 2004)
This article is a video presentation of an interview with Buz Brock at the 12th SNDE conference in Atlanta Georgia on March 12, 2004. The interview includes 15 questions on topics ranging from nonlinear dynamics, ecological modeling, and heterogenous agents.
Keywords: C61; 330; nonlinear dynamics; heterogenous agents; ecology; bio-diversity; Nichtlineare dynamische Systeme; Biodiversität; Umweltökonomik